Enabling equitable access to public transport information to enhance hybrid system use in Cape Town, South Africa - Ryseck, Bianca Beatrice (Department of Civil Engineering, 2023)
Though previously unscheduled public transport services were often seen as incompatible with equitable mobility goals, emerging cities are increasingly seeking to integrate these with new scheduled services to form hybrid public transport systems. In contrast to the abundance of services available, there is little information available to plan multimodal journeys across the hybrid system, limiting users' abilities to best use the system to meet their needs. This thesis investigated, through mixed research methods framed within Amartya Sen's capability approach, how to enable equitable access to public transport information on the hybrid system through information and communications technology. The research focussed on captive public transport users in the context of Cape Town, South Africa. Using (n=22) semi-structured interviews, candidate passenger information types for planning hybrid journeys across various scenarios were identified. A best-worst scaling study was undertaken (n=413) to gain a representative understanding of the least and most useful information types. A stated preference choice model was applied (n=501) to investigate what minimum information is required to make use of the hybrid network to access mobility opportunities in non-routine scenarios. The most useful information types were represented as different levels of certainty. These information types were: (1) frequency, (2) fare cost, (3) departure time, (4) arrival time, (5) safety walking to/from a station/stop, (6) safety onboard, and (7) safety while waiting at a stop. A further passenger survey (n=536), together with available secondary data, was analysed to gauge access to technologies and skills related to transport information use cases. This research found that none of the information types at the quality level desired is currently evenly available across the hybrid system, and no official information sources have the capacity to equitably reach captive users given current technological capabilities. The combination of gaps in information provision and adequate communication methods hinders users' informational capabilities to plan journeys that best meet their needs and preferences, and consequentially limits their access to opportunities through mobility. Strategies for understanding information needs, collecting the data necessary, and opening this data to the public through portals provide the adaptability and flexibility needed to deliver sustainable solutions.